The relationship of psychophysiological characteristics karate qualifications in light weight category with the effective implementation of kick leg techniques in upper level of the opponent - Vladimir Saienko (Слобожанський науково-спортивний вісник, 2015)
Purpose: set the density of the relationship of psycho-physiological characteristics of karate qualifications in light weight category with the efficiency of the implementation of kick leg techniques in the upper level of the opponent. Material and Methods: The study involved thirty highly skilled karatekas in light weight category. Conducted pedagogical and psychophysiological testing, carried out an analysis of competitive actions, carried out a special analysis of scientific and methodical literature, applied the methods of mathematical statistics. Results: The degree of correlation between the obtained numerical results of psycho-physiological characteristics and indicators of the effectiveness different types of gradient kicking karate qualifications in light weight category in upper level of the opponent. Conclusions: karatekas high qualifications in light weight category, the higher the strength of neural processes in the processing of information in the imposed rhythm, the more reliable in a competitive match under implementation methods kick leg them with maximum power and speed-up in upper level of the opponent, and at the higher they characteristic of functional mobility of nervous processes in the processing of information in the imposed rhythm, the greater the likelihood of fighters attacking moves fast.